2016
DOI: 10.1016/j.jcomdis.2016.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Self-perceived competence and social acceptance of young children who stutter: Initial findings

Abstract: Purpose The goals of this study were to determine whether young children who stutter (CWS) perceive their own competence and social acceptance differently than young children who do not stutter (CWNS), and to identify the predictors of perceived competence and social acceptance in young speakers. Method We administered the Pictorial Scale of Perceived Competence and Social Acceptance for Young Children (PSPCSA; Harter & Pike, 1984) to 13 CWS and 14 CWNS and examined group differences. We also collected infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…The SDs are consistent with scale sensitivity to individual differences in perceived competence and acceptance among young children . This instrument is widely used for research with preschool-aged children, including the measurement of the effects of intellectual disability, stuttering, and obesity on self-concept and the effects of physical activity programs on self-concept …”
Section: Methodsmentioning
confidence: 57%
See 1 more Smart Citation
“…The SDs are consistent with scale sensitivity to individual differences in perceived competence and acceptance among young children . This instrument is widely used for research with preschool-aged children, including the measurement of the effects of intellectual disability, stuttering, and obesity on self-concept and the effects of physical activity programs on self-concept …”
Section: Methodsmentioning
confidence: 57%
“…in perceived competence and acceptance among young children. 22 This instrument is widely used for research with preschool-aged children, including the measurement of the effects of intellectual disability, stuttering, and obesity on self-concept [31][32][33] and the effects of physical activity programs on self-concept. [34][35][36] There are 6 pairs of pictures for each domain, presented in a 2-alternative format.…”
Section: Key Pointsmentioning
confidence: 99%
“…Negative social experiences could have consequences in terms of self-doubt about their ability to be competent communicators and lower self-esteem. In this regard, students who perceived their stuttering as more severe scored lower on the specific domains of self-esteem, social acceptance, and the ability to make close friends (Adriaensens, Beyers, & Struyf, 2015), and lower stuttering frequency was associated with greater perceived social acceptance (Hertsberg & Zebrowski, 2016).…”
Section: The Relationship With Teachers In Children Who Stuttermentioning
confidence: 94%
“…On the contrary, other studies report no differences between the two groups, as for self-esteem and self-perception. Hertsberg and Zebrowski (2016), who examined children from 4 to 6 years old by using the Pictorial Scale of Perceived Competence and Social Acceptance for Young Children (Harter and Pike,1984) reported no significant differences between children with CoFD and their controls as far as self-perception is concerned. Yovetich et al (2000), by using the Culture Free Self-Esteem Inventory, 2 nd Edition (Battle, 1981), found similar reports of self-esteem in children whether they had CoFD or not, and, thus, they concluded that CoFD does not play an important role in self-esteem development.…”
Section: Introductionmentioning
confidence: 99%